Challenges of the Banking systems of Oil Exporting Countries (Case of Azerbaijan) - Mammadyarov, Aliyar (2008)
Recent trends of increasing oil prices in world commodity markets lead to the notion that it is a good chance for oil exporting countries to accelerate development of their national economies and to strengthen their financial systems. At the same time, the impact of instability of commodity pricing process (especially in case of unrenewable, limited natural recourses) to national economies is a matter of concern both for buyers and sellers of oil. Moreover, in oil exporting countries these concerns are also being pressured by such side-effects of oil revenues such as the 'Dutch Disease'. This work investigates the impacts that the above mentioned problems may have on soundness of banking industry in oil exporting countries. It can be of interest to policy makers and people responsible for the financial stability, especially in the developing countries.